Johor : abode of development? - Hutchinson, Francis E.; Serina Rahman (Singapore : ISEAS-Yusof Ishak Institute, 2020)
In 1990, the Malaysian state of Johor-along with Singapore and the Indonesian island of Batam-launched the Growth Triangle to attract foreign direct investment. For Johor, this drive was very successful, transforming its economy and driving up income levels. Today, Johor is one of Malaysia's "developed" states, housing large clusters of electrical and electronics, food processing, and furniture producing firms. While welcome, this structural transformation has also entailed important challenges and strategic choices. After three decades, Johor's manufacture-for-export model is under question, as it faces increasing competition and flat-lining technological capabilities. In response, the state has sought to diversify its economy through strategic investments in new, mostly service-based activities. Yet, Johor retains pockets of excellence in traditional sectors that also require support and policy attention. The state's economic transformation has also been accompanied by far-reaching political, social, and environmental change. Not least, Johor's growing population has generated demand for affordable housing and put pressure on public services. The strain has been exacerbated by workers from other states and overseas. These demographic factors and large-scale projects have, in turn, put stress on the environment. Building on earlier work by the ISEAS - Yusof Ishak Institute on the Singapore-Johor-Riau Islands Cross-border Region, this book focuses on this important Malaysian state, as it deals with important domestic challenges on one hand and strives to engage with international markets on the other.
Title from publisher's bibliographic system (viewed on 08 Dec 2020).
Keywords: Investments, Singaporean -- Malaysia -- Johor; Industries -- Malaysia -- Johor; Johor (Malaysia) -- Economic conditions; Johor (Malaysia) -- Politics and government